Impacts of family environment on adolescents’ academic achievement: The role of peer interaction quality and educational expectation gap - Zhao, Lie; Zhao, Wenlong (Frontiers in Psychology, 2022)
The current study uses a two-wave longitudinal survey to explores the influence mechanism of the family environment on adolescents’ academic achievement. The family environment is measured by parents and children’s reports, including family atmosphere, parent–child interaction, and family rules, to reveal the mediating effect of adolescents’ positive or negative peers between the family environment and academic achievement, and whether the gap between self- and parental educational expectation plays a moderating effect. This study uses the data of the China Education Panel Study (CEPS); the survey samples include 9,449 eighth-grade students (Mage = 13.55 years, SD = 0.70), establishing a multilevel moderated mediating effect model. The results showed (1) the family environment and peer interaction quality can positively predict adolescents’ academic achievement. (2) Using the KHB test, peer interaction quality plays a partial mediating role in the process of family environment positively affecting academic achievement, and the mediating ratio is 27.5%. (3) The educational expectation gap moderates the effect of the family environment on academic achievement and also on peer interaction quality. Therefore, from the perspective of environment and important others, to correctly grasp the academic achievement of junior high school students in the process of socialization, it is necessary to recognize that the family environment, peer interaction quality, and educational expectation gap play an important role.